2021
DOI: 10.1002/adfm.202103893
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Induced Graphene Assisting Self‐Conversion Reaction for Sulfur‐Free Aqueous Cu‐S Battery

Abstract: In aqueous/nonaqueous metal-sulfur batteries, sulfur-based redox couple exhibits significant challenges mainly due to its low electrochemical kinetics, potential shuttle effect, and large volume change. Although massive researches have been conducted to optimize or replace metal anode and cathode composite, major challenges caused by the dependency on sulfurbased redox couple still remain. In this study, a novel redox couple of CuS/ Cu 2 S, which provides the same theoretical capacity (based on conventional S/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 44 publications
2
30
0
1
Order By: Relevance
“…Moreover, the authors concluded that the large number of defects and heteroatoms in the LIG lowered the nucleation potential barrier of Li, thus promoting stable cycling of the Li-metal anode. As a result, this approach allowed the Li-metal anode to achieve a high coulombic efficiency of 99% at 1 mA cm −2 and a high cycle life of 400 h. Yang et al [ 149 ] proposed a novel CuS/Cu 2 S aqueous solution cell. They used a composite of LIG mixed with sulfur as the cathode of this cell.…”
Section: Applications Of Ligmentioning
confidence: 99%
“…Moreover, the authors concluded that the large number of defects and heteroatoms in the LIG lowered the nucleation potential barrier of Li, thus promoting stable cycling of the Li-metal anode. As a result, this approach allowed the Li-metal anode to achieve a high coulombic efficiency of 99% at 1 mA cm −2 and a high cycle life of 400 h. Yang et al [ 149 ] proposed a novel CuS/Cu 2 S aqueous solution cell. They used a composite of LIG mixed with sulfur as the cathode of this cell.…”
Section: Applications Of Ligmentioning
confidence: 99%
“…However, the limitations of the organic electrolyte itself (e.g., low ionic conductivity, flammability, and volatility) ( 6 8 ), the shuttle effect of polysulfide, the lithium dendrite, and large-volume changes of the battery system in the process of discharge and charge are all urgent problems to be solved in organic Li-S batteries ( 9 12 ). In this case, researchers have begun to focus on high ionic conductivity, nonflammable, and chemically mild aqueous metal-sulfur batteries in recent years ( 13 – 20 ). In these studies of aqueous metal-sulfur batteries, Cu-S, Fe-S, and Zn-S systems have attracted much attention due to their high reversible capacity and excellent cycling performance in aqueous electrolyte.…”
mentioning
confidence: 99%
“…In these studies of aqueous metal-sulfur batteries, Cu-S, Fe-S, and Zn-S systems have attracted much attention due to their high reversible capacity and excellent cycling performance in aqueous electrolyte. Meanwhile, optimization of the cathode material ( 14 ) and electrolyte ( 17 ) of aqueous metal-sulfur batteries is also being carried out gradually. However, no new metal-sulfur chemistry was found to undertake the energy storage task, and the exploration of new systems seems to have entered a bottleneck period.…”
mentioning
confidence: 99%
“…To address the above‐mentioned issues, many functional carbonaceous composites (carbon nanotubes/fibers, 6,7 graphene 8 and nonmetal elements doped carbonaceous 9 ) have been designed as sulfur host materials for enhancing electron transfer and dissolved polysulfides confinement. Although these well‐designed host materials can impressively improve the electrochemical properties of sulfur cathode, the weak physical interaction between the non‐polar carbon surface and the polar polysulfides can only decrease the diffusion rate and eventually the polysulfides still migrate out of the carbon host to cause shuttle effect, which resulting in sluggish redox kinetics of the lithium polysulfides 10 …”
Section: Introductionmentioning
confidence: 99%
“…1,2 However, the poor conductivity of sulfur in LSBs, the tricky polysulfides shuttle can cause loss of active sulfur mass and corrosion of the lithium anode, and the migration of polysulfides can damage the electrode structure, further causing degradation of electrochemical performance and rapid decay of capacity. [3][4][5] To address the above-mentioned issues, many functional carbonaceous composites (carbon nanotubes/ fibers, 6,7 graphene 8 and nonmetal elements doped carbonaceous 9 ) have been designed as sulfur host materials for enhancing electron transfer and dissolved polysulfides confinement. Although these well-designed host materials can impressively improve the electrochemical properties of sulfur cathode, the weak physical interaction between the non-polar carbon surface and the polar polysulfides can only decrease the diffusion rate and eventually the polysulfides still migrate out of the carbon host to cause shuttle effect, which resulting in sluggish redox kinetics of the lithium polysulfides.…”
Section: Introductionmentioning
confidence: 99%